The Role of Copulas in the Housing Crisis - Zimmer, David M. (The Review of Economics and Statistics, 2012)
Due to its simplicity and familiarity, the Gaussian copula is popular in calculating risk in collaterized debt obligations, but it imposes asymptotic independence such that extreme events appear to be unrelated. This restriction might be innocuous in normal times, but during extreme events, such as the housing crisis, the Gaussian copula might be inappropriate. This paper explores various copula specifications and finds that the degree to which housing prices are related based on the Gaussian copula is too small compared with real housing price data. © 2012 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.